2013
DOI: 10.5194/hessd-10-6515-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of hydrologic signatures in two agricultural watersheds in east-central Illinois: legacies of the past to inform the future

Abstract: Historically, the central Midwestern US has undergone drastic anthropogenic land use change, having been transformed, in part through federal government policy, from a natural grassland system to an artificially-drained agricultural system devoted to row cropping corn and soybeans. Current federal policies are again influencing land use change in this region with increased corn acreage and new biomass crops proposed as part of an energy initiative emphasizing biofuels. To better address these present an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…When Yaeger et al . () compared Miscanthus to corn and soya bean grown in the American mid‐West, they found that Miscanthus had effectively a 2‐month longer season of transpiration which meant a reduction in soil water reserves during low rainfall. This reduction can be exacerbated by the dense canopy of Miscanthus which intercepts more rain allowing more evaporation at the leaf level and less throughfall to the soil compared to some other crops.…”
Section: Water Balancementioning
confidence: 99%
“…When Yaeger et al . () compared Miscanthus to corn and soya bean grown in the American mid‐West, they found that Miscanthus had effectively a 2‐month longer season of transpiration which meant a reduction in soil water reserves during low rainfall. This reduction can be exacerbated by the dense canopy of Miscanthus which intercepts more rain allowing more evaporation at the leaf level and less throughfall to the soil compared to some other crops.…”
Section: Water Balancementioning
confidence: 99%
“…Socio-hydrology relies heavily on understanding historical processes in order to learn how the present hydrological and social situation has been established, what the inherent fluctuation in the system is and how it has been dealt with (successfully or unsuccessfully) in the past (Yaeger et al, 2013;Srinivasan et al, 2012). In the typical case, historical sociohydrological investigations can be of quantitative nature as long as there are quantitative hydrological records available, and turns qualitative or model-based in the lack of these.…”
Section: Socio-hydrologymentioning
confidence: 99%
“…Without information on historic changes, it might be assumed that the hydrological situation is static over time (James, 1999), while given information on earlier states of a watershed, the changes can be used to inform hydrological models (Yaeger et al, 2013).…”
Section: Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…and moving in a counter‐clockwise direction, the green arrow captures a critical linkage from human actions in the catchment to the lake via the hydrologic fate and transport of nutrients and sediment (Yaeger et al. , Rabotyagov et al. ).…”
Section: Conceptual Framework: Focus On Feedbacksmentioning
confidence: 99%